Carta de José de Diego, Luis Sánchez Morales y Roberto H. Todd - Todd, Roberto H.; Colton, George R. (My University, 1912)
Carta de José de Diego, Luis Sánchez Morales y Roberto H. Todd felicitandolo.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Republican National Committee; Comité Nacional Republicano